Corporate Governance and Performance: The Divergence of Operating and Share Performance - Taşkın, F. Dilvin; Okur, Mustafa Reha (International Journal of Contemporary Economics and Administrative Sciences, 2018)
Corporate governance principles are trying to ensure reliable and well functioning firms and sound financial systems, thus well-governed firms are expected to be performing better than their counterparts. The aim of this paper is to analyze the impact of corporate governance applications on operating performance and share performance of companies that are traded in Borsa Istanbul for the period 2007-2014. In order to understand the impact of corporate governance traits on share performance, we assume that we buy and hold the stock for 1 year and sell it at the end of the accounting period to match it with the accounting data and panel regressions are run to analyze the factors that have significant explanatory power over operating and share performance. According to the results, the corporate governance traits do not affect stock returns, but have a significant explanatory power over operating performance, measured by ROA and ROE. This divergence shows that good governance results with superior operating performance, however governance benefits are not priced by the investors. The paper has significant implications since it analyses one of the most attractive emerging equity markets, namely Borsa Istanbul which has approximately sixty percent share of foreign investors. The results are important for both policy makers and for the broad range of investors that are players in the market.